1. Identification of gastrointestinal parasites in bird white-rumped shama (copsychus malabaricus) kept by bird lovers in the Pariaman city, west sumatera - Lian Varis Riandi; M. Ikral; Yudha Fahrimal (Jurnal Medika Veterinaria, 2021)
Bird White-Rumped Shama (Copsychus malabaricus) is one of the many singing birds with many lovers. Like other animals, both free-living and chage, white-rumped shama can be attacked by diseases caused by bacteria, viruses, and endoparasites. This study aims to identify the types of endoparasites in white-rumped shama kept by bird lovers in City of Pariaman, totaling 50 white-rumped shama from bird lovers in City of Pariaman. This research was conducted at the Parasitology Laboratory of the Faculty of Veterinary Medicine Universitas Syiah Kuala. Samples were examined using the floating method, the Borray sedimentation method, the formol-ether sedimentation method, and the Ziehl-Neelsen fast acid modification. From the examination results using the floating method, eggs were obtained from two types of endoparasitic worms, namely Heterakis sp. and Capillaria sp. In examining the modified Borray sedimentation method, the formol-ether sedimentation method and the modified Ziehl-Neelsen fast acid method, no eggs of nematodes, trematodes and cestodes were found. This study showed that 5 out of white rumped shama feces samples were infected with endoparasites. The types of endoparasites found from the white-rumped shama kept by bird lovers in Pariaman are nematodes of the genus Heterakis sp. and Capillaria sp. Based on the research results, it can be concluded that the white-rumped shama kept by bird lovers in City of Pariaman is infected with endoparasites.